2021
DOI: 10.3390/ijms222111652
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Type 2 Diabetes: Novel Biomarkers for Risk Assessment?

Abstract: Diabetes is a severe threat to global health. Almost 500 million people live with diabetes worldwide. Most of them have type 2 diabetes (T2D). T2D patients are at risk of developing severe and life-threatening complications, leading to an increased need for medical care and reduced quality of life. Improved care for people with T2D is essential. Actions aiming at identifying undiagnosed diabetes and at preventing diabetes in those at high risk are needed as well. To this end, biomarker discovery and validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 169 publications
(464 reference statements)
0
15
0
Order By: Relevance
“…However, to our knowledge, this is the first study that investigates the association between blood DNA methylation with type 2 diabetes prospectively. According to the meta-analysis conducted by Raciti et al [ 16 ], which was published by the end of 2021, all the previous studies in blood DNA methylation were either cross-sectional [ 10 , 44 , 47 50 ], focused on targeted genes rather than epigenome-wide [ 46 , 51 , 52 ], or focused on global DNA methylation, rather than site-specific methylation [ 53 ]. Although an EWAS conducted in a European population [ 45 ] evaluated incident diabetes, they did not account for time to event in the EWAS models, which were conducted using a logistic regression (with a dichotomous outcome) rather than survival analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, this is the first study that investigates the association between blood DNA methylation with type 2 diabetes prospectively. According to the meta-analysis conducted by Raciti et al [ 16 ], which was published by the end of 2021, all the previous studies in blood DNA methylation were either cross-sectional [ 10 , 44 , 47 50 ], focused on targeted genes rather than epigenome-wide [ 46 , 51 , 52 ], or focused on global DNA methylation, rather than site-specific methylation [ 53 ]. Although an EWAS conducted in a European population [ 45 ] evaluated incident diabetes, they did not account for time to event in the EWAS models, which were conducted using a logistic regression (with a dichotomous outcome) rather than survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As the prediabetes period is long and the diabetes diagnostic criteria are established in advanced phases, DNA methylation dysregulations might be a powerful biomarker for early detection [ 15 ], which might help with early treatment and to reduce healthcare costs. In addition, DNA methylation has been suggested to have a higher predictive ability than genetics for type 2 diabetes in high-risk subjects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…But in patients with cancers in all age groups, it was downregulated. Though in the case of the 3 younger people aged (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years tpm was around 35 while in older people (81-100) it was much less (Figure 5E). Similarly surveying nodal metastasis, we found that the HbA1 value decreases as nodal stages (N0, N1, and so on) advance, but it's higher in people without the disease (Figure 5F).…”
Section: Analysis Of the Oncoinformatic Parametersmentioning
confidence: 94%
“…It is necessary to take steps to find undiagnosed diabetes and prevent it in people who are at high risk. More recent research indicates that changes in DNA methylation may even more significantly contribute to the risk of T2D than genetic variability and may be a useful indicator of T2D risk [22]. In many human cancers, including bladder cancer, abnormal promoter methylation (also known as hypermethylation) is a key mechanism for suppressing tumor suppressor genes and other cancer-associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation may affect gene expression without affecting DNA sequencing and consequently alter various normal biological functions. Moreover, DNA methylation has been linked to the etiology of many diseases, including cancer [31], kidney disease [32], diabetes type 2 [33], psychiatric disorders [34], and sepsis [35]. Additionally, it has been reported that DNA methylation could be affected by estrogen treatment and is considered an explanation for gene expression changes by treatment in experimental models [36].…”
Section: Cns Tumor Classification Using Dna Methylation Arraysmentioning
confidence: 99%